O discurso pedagógico nos jogos de simulação de vida e ambientes por telefone celular: o jogo the sims2 - Baron, Roberto (2011)
This dissertation aims to analyze, under the gaze of Discourse Analysis of the French line, the possibility of a pedagogical discourse embedded in an electronic game that simulate life, characters and environments (played on computer or mobile phone) to support the processes of teaching and learning. The analysis seeks by tools and opportunities to discuss the possibility of rupture of the authoritarianism of pedagogical discourse. Among the reasons that prompted the researcher to proceed with the analysis were the popularization of resources that we can find in an electronic game that simulate life, characters and environments including cognitive resources, the ability to play the game through technologies like the mobile phone and computer, contradictions between laws that banning cell phone and computer games at school, and the educational approach provided by the Brazilian federal constitution of 1988. The features that may help do difference with a electronic game that simulate life, characters and environments in the teaching and learning processes of the schools are the interaction, simulation, challenges, problem solving, and production of visual and written texts. The concepts of Education, Ideology, Discourse Analysis, typology of discourse, pedagogical discourse, electronic discourse and the discursive trends are the scientific theory support. In order to contextualize the game The Sims2 in the world of games was created a description of a history of games since ancient times until the advent of electronic games. The analysis was described from the images, simulation and challenge tools that show the Discourses of the game. The typology of Discourse developed by Eni Orlandi (2009) explains about the types of operation of the discursive trends of the discourses inserted in them (the images and tools of the game) that are the base for the comparison between the discourses that are produced of discursive positions of the game makers and game players with the discourse of school, the pedagogical discourse. In the end of this dissertation are suggested proposals, challenges and also the conclusions about the analysis that may help teachers and learners when electronic games that simulate life, characters and environments, such as "The Sims2" from EA Games, may be played in the schools as a tool that helps teachers and students in the teaching and learning processes